Tatbiq al-Thariqoh al-Mubasyirah fi al-Fashl al-Syarqi al-Tsani bi Markaz Arabiyah Pare Kediri - Firdaus, Rousul (Al-Wazan: Journal of Arabic Education, 2024)
The direct method is one of the popular language teaching methods that has been passed down through generations. One institution that implements and develops this method is Markaz Arabiyah Pare Kediri, specifically in the Syarqi Tsani class. The application of the direct method in Arabic language learning at this course institution is considered appropriate based on its characteristics and implementation procedures. The research method employed is descriptive qualitative, and the objectives of this study are (1) to understand the history and development of the direct method in language learning, (2) to explore the application of the direct method in the Syarqi Tsani class at Markaz Arabiyah Pare Kediri, and (3) to identify the supporting and inhibiting factors of the direct method implementation in Arabic language learning at the Syarqi Tsani class of Markaz Arabiyah Pare Kediri. The research findings indicate that (1) the direct method emerged in the early 17th century, (2) the application of the direct method in the Syarqi Tsani class is developed by selecting contemporary themes and supported by a language-rich environment, and (3) supporting factors include student interest and motivation, competent teaching staff, and a highly supportive environment, while inhibiting factors include insufficient supervision in unplanned situations, suboptimal language environment, and occurrences of bilingualism